HBR's 10 must reads on performance management. (Boston, Massachusetts : Harvard Business Review Press, 2023)
"For decades, performance management has been seen as an annual chore by managers and HR alike. But this process is changing, and there are ways to make it more effective for your organization and more useful for employees. If you read nothing else on performance management in your organization, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you assess performance more accurately, have more-effective feedback conversations, and encourage the growth of your employees. This book will inspire you to learn where current performance management processes are falling short; create sustainable performance across the organization; deliver feedback that motivates and develops your team members; help your people reach their professional goals; identify your role in an employee's poor performance; and evaluate performance fairly, even in a remote environment"--
The Performance Management Revolution / by Peter Cappelli and Anna Tavis -- Reinventing Performance Management / by Marcus Buckingham and Ashley Goodall -- Getting 360-Degree Feedback Right / by Maury A. Peiperl -- The Set-Up-To-Fail Syndrome / by Jean-François Manzoni and Jean-Louis Barsoux -- Job Sculpting: The Art of Retaining Your Best People / by Timothy Butler and James Waldroop -- Performance Management Shouldn't Kill Collaboration / by Heidi K. Gardner and Ivan Matviak -- The Happy Tracked Employee / by Ben Waber -- Don't Let Metrics Undermine Your Business / by Michael Harris and Bill Tayler -- "Numbers Take Us Only So Far" / by Maxine Williams -- Managers Can't Do It All / by Diane Gherson and Lynda Gratton -- Creating Sustainable Performance / by Gretchen Spreitzer and Christine Porath.
Includes index.
Description based on online resource; title from digital title page (viewed on May 22, 2023).
WorldCat record variable field(s) change: 050
Keywords: Employees -- Rating of; Goal setting in personnel management; Performance; Industrial management; Success in business; Employees -- Rating of; Goal setting in personnel management; Industrial management; Performance; Success in business; elektronické knihy; electronic books